Communication Strategy Used by The Students of Vocational School on Speaking Class - Prasetiyowati, Eni (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2023)
Some problems usually are faced by the students when learning speaking in English as a foreign language. That difficulties also faced by the students of vocational school when they learn in speaking class. In their presentation or talk as performance, they have lack for delivering idea in their speaking. All of them are faced by them since there are difficulty of the target language owing to their hesitation and unfamiliar of vocabulary. Meanwhile, they have to present their idea in the talk as performance in speaking class to the audiences or their friends. Whereas, as students of vocational school majoring tourism, they are expected to have good ability on speaking English. Thus, when facing that problem, it is needed a strategy which can solve their difficulty in speaking. Communication strategy can be used by the students when they faced some difficulties in their speaking. It is students’ attempts involving some strategies in communication which can make the utterances can be understandable and meaningful for achieving communication goal. In addition, the communication strategy is crucial way which can be implemented in the teaching speaking since it can help the students for learning speaking. This paper concerns on the kinds of communication strategies used by the students of vocational school and the process of communication strategy on the speaking class. The qualitative study is conducted in this study since the data are collected are in the form of word. Finally, the result of this study can give new insight for the teachers that communication strategy can be used not only for daily communication but also for teaching speaking.